Telestroke Assessment With Perfusion CT Improves the Diagnostic Accuracy of Stroke vs. Mimic - Tran, Lucinda; Lin, Longting; Spratt, Neil; Bivard, Andrew; Chew, Beng Lim Alvin; Evans, James W.; O'Brien, William; Levi, Christopher; Ang, Timothy; Alanati, Khaled; Pepper, Elizabeth; Garcia-Esperon, Carlos; et al. (Frontiers in Neurology, 2021)
Background and Purpose CT perfusion (CTP) has been implemented widely in regional areas of Australia for telestroke assessment. The aim of this study was to determine if, as part of telestroke assessment, CTP provided added benefit to clinical features in distinguishing between stroke and mimic, and between transient ischaemic attack (TIA) and mimic. Methods We retrospectively analysed 1513 consecutively recruited patients referred to the Northern New South Wales Telestroke service, where CTP is performed as part of telestroke assessment. Patients were classified based on the final diagnosis of stroke, TIA, or mimic. Multivariate regression models were used to determine factors which could be used to differentiate between stroke and mimic and between TIA and mimic. Results There were 693 strokes, 97 TIA and 259 mimics included in the multivariate regression models. For the stroke vs mimic model using symptoms only, the area under the curve (AUC) on the receiver operator curve (ROC) was 0.71 (95% CI 0.67-0.75). For the stroke vs mimic model using the absence of ischaemic lesion on CTP in addition to clinical features, the AUC was 0.90 (95% CI 0.88-0.92). The multivariate regression model for predicting mimic from TIA using symptoms produced an AUC of 0.71 (95% confidence interval 0.65-0.76). The addition of absence of an ischaemic lesion on CTP to clinical features for the TIA vs mimic model had an AUC 0.78 (95% CI 0.73-0.83) Conclusions In the telehealth setting, absence of an ischaemic lesion on CTP adds to the diagnostic accuracy in distinguishing mimic from stroke, above that from clinical features.